THE IMPACT OF RENEWABLE ENERGY PRODUCTION ON GREENHOUSE GAS EMISSIONS IN ROMANIA - LIVIU-VALENTIN VLĂDUCU; CLAUDIU-FLORENTIN LĂCEANU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2022)
Romania's greenhouse gas (GHG) emissions come largely from the energy sector, including the energy production sector. In 2019, the energy sector contributed 66.45% of total GHG emissions. Energy strategies and policies adopted at national level are the primary tool for setting goals that should help reduce the impact of the energy sector on the environment. The nationally set targets for the promotion of renewable energy production need to be complemented by measures to increase energy efficiency. These measures must lead, on the one hand, to an increase in the share of electricity production from renewable sources in final energy consumption, but also to a reduction in the use of fossil fuels. Fossil fuels used in the production of electricity are mostly low-reserve hydrocarbons, the combustion of which emits significant amounts of greenhouse gases into the atmosphere, which have the effect of increasing the average temperature of the atmosphere and the occurrence of climate change. Unlike fossil fuels, renewable sources are inexhaustible and available in nature, and energy production from these sources does not contribute to increased greenhouse gas emissions. This analysis aims to examine the correlation between the change in the level of greenhouse gas emissions depending on the change in energy intensity and the share of E-RES in gross final energy consumption, recorded annually at the national level, in the period 1995-2019.